Multi-scale flow structure of a strike-slip tectonic setting: A self-similar model for the Liquiñe-Ofqui Fault System and the Andean Transverse Faults, Southern Andes (39–40°S). (July 2022) - Roquer, Tomás; Arancibia, Gloria; Crempien, Jorge G.F.; Mery, Domingo; Rowland, Julie; Sepúlveda, Josefa; Veloso, Eugenio E.; Nehler, Mathias; Bracke, Rolf; Morata, Diego
Highlights: We conducted a multi-scale length survey in regional-scale faults and lineaments, and meso‑ and micro-scale fractures in the Southern Andes. We determined self-similar length density distributions, two-point correlation functions and distances to the closest larger neighbor across 9 orders of magnitude (10 4 -10 −4 m). Spacing density distributions between surficial active geothermal areas follows a power-law across 6 orders of magnitude (10 5 -10° m). A multi-scale model for the flow structure of the uppermost crust is proposed (e.g. <1 km depth). Abstract: The flow structure of a brittle crustal volume is defined by the multi-scale geometric and hydraulic properties of its fracture meshes. The length density distribution n(L, l) and the transmissivity distribution K(L, l) control the hydrologic scaling, where l is fracture length and L is the system size. The flow structure might display at most three key hydrologic scales: the connection scale, above which flow is focused in few critical paths; the channeling scale, above which flow is distributed in several paths; and the homogenization scale, above which permeability approaches a constant value. According to these scales, the hydrological structure could be distributed or clustered, thus having a clear impact in geothermal exploration campaigns and reservoir modeling. In this work, we determine the multi-scale flow structure for the Liquiñe-Ofqui Fault System (LOFS) and the Andean Transverse Faults (ATF) in the Southern Andes, by establishing the hydrologic scaling they follow. Using fractal statistics, we integrated geological data at the regional, meso‑ and micro-scale, including image analysis from X-ray microtomography. Our results suggest a self-similar, dense network with n(L, l) ∼ l −a and a = 2.6–2.9, from the regional scale where the LOFS and ATF interact to the meso‑ and micro-scale within highly fractured areas of the LOFS. Scaling models are constrained by the length distribution, and other power-law functions reflecting the geometric arrangement of fractures, as well as the spatial distribution of superficial geothermal occurrences. Thus, we expect the hydrologic scaling to depend on the transmissivity distribution. Lognormal transmissivity distribution yields a permeability increase with scale, from the connection to the homogenization scales; whereas power-law transmissivity distribution yields a permeability increase from the connection scale without a limiting value. Approximations of the connection scale are around 10 −3 –10 0 m; the channeling scale, around 10 0 –10 4 m; and if the homogenization scale exists, it should be equal or greater than 10 3 –10 4 m. Finally, the results presented here could to define the internal architecture of fracture meshes in fault-controlled fluid flow, and be used to select an appropriate hydrologic model according to the analyzed scale. Therefore, these findings must be taken into consideration in future geothermal prospecting, modeling and exploitation.